Clinical and Radiological Evaluation of Cleidocranial Dysplasia in Two Trinidadian Siblings - Bissoon, AK (West Indian Med J, 2014)
Cleidocranial dysplasia is a rare developmental disorder of the skeleton and teeth that may be inherited as an autosomal dominant trait or occur spontaneously. This is a report of two Trinidadian, East Indian brothers aged 13 and 15 years referred from a private dental practice with the chief complaint of retained deciduous teeth. Subsequent clinical and radiographic investigations led to the diagnosis of cleidocranial dysplasia. The clinical and radiographic findings are discussed.